2020
DOI: 10.3126/mjpahs.v3i1.31925
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Caesarean Section in Matri Shishu Miteri Hospital of Gandaki Province

Abstract: Background: Caesarean section (CS) is one of the commonest obstetrics procedure to reduce the risks for mother and fetus when vaginal delivery is not anticipated. The objective of the study was to determine the rate and clinical indication of Caesarean section. Materials and Methods: This was a hospital based descriptive retrospective study done within a time frame of a year (from Shrawan 2075 BS to Ashad 2076 BS; 17 July 2018 to July 16 2019) in Matri Shishu Miteri Hospital, Pokhara, Nepal. The total n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Unfortunately, these criteria for VBAC are often scarce in most places in low-resource countries. 104 As reported by several previous studies, our review documents many other common key indications for CS: APH/placenta previa/abruption, 22,96,101,103 CPD, 22,95,96,100,103 HDP, 22,95,96,103 failed induction, 22,96,100,103 NPOL, 95,96,[100][101][102][103] oligohydramnios, 95,100,103 multiple pregnancy, 22,95,101,103 malpresentation, 95,96 breech presentation, 22,100,103 and IUGR, 95,101 Similarly, CPD is found to be a key indicator for elective CS. 95,97,98 emergency CS, 95,96,98 primary CS, 99 repeat CS 99 and CS in primigravida.…”
Section: Key Indications For Cs In South Asiamentioning
confidence: 75%
See 1 more Smart Citation
“…Unfortunately, these criteria for VBAC are often scarce in most places in low-resource countries. 104 As reported by several previous studies, our review documents many other common key indications for CS: APH/placenta previa/abruption, 22,96,101,103 CPD, 22,95,96,100,103 HDP, 22,95,96,103 failed induction, 22,96,100,103 NPOL, 95,96,[100][101][102][103] oligohydramnios, 95,100,103 multiple pregnancy, 22,95,101,103 malpresentation, 95,96 breech presentation, 22,100,103 and IUGR, 95,101 Similarly, CPD is found to be a key indicator for elective CS. 95,97,98 emergency CS, 95,96,98 primary CS, 99 repeat CS 99 and CS in primigravida.…”
Section: Key Indications For Cs In South Asiamentioning
confidence: 75%
“…99 Recent studies have reported that previous CS is the key leading indication of CS. 22,[100][101][102][103] The growing number of primary CS may influence the decisionmaking around mode of birth. The majority of pregnant women who have a history of previous CS would decline vaginal birth after CS (VBAC).…”
Section: Key Indications For Cs In South Asiamentioning
confidence: 99%